Effect of Different Root Canal Drying Protocols on the Bond Strength of Two Bioceramic Sealers - Frasquetti, Karine Santos; Piasecki, Lucila; Kowalczuck, Alexandre; Carneiro, Everdan; Westphalen, Vânia Portela Ditzel; Neto, Ulisses Xavier da Silva (European Journal of Dentistry, 2022)
Objectives This study evaluated in vitro the effect of two different drying protocols on the dentin bond strength of two different bioceramic sealers (Sealer Plus BC [SP] and Bio C Sealer [BCS]). Bond strength and failure mode were evaluated according to the sealer, drying protocol, and root canal third.Materials and Methods Sixty extracted human mandibular single-rooted premolars were selected after anatomical standardization. The crowns were sectioned and root canals were prepared. Roots were randomly divided into four groups (n = 15 each). Each group was assigned a combination of one of the evaluated sealers (SP or BCS) and one of the drying protocols: canals dried with paper points (PP) or irrigation with saline followed by aspiration with silicon cannulas (IA). Obturations were performed using a single-cone technique. The teeth were temporized and stored for 7 days (100% humidity, 37°C). Roots were cut to obtain 2 mm thick discs for each third (coronal, middle, and apical). Push-out tests were performed on a universal testing machine, and the bond strength (MPa) of each specimen was calculated by dividing the load (N) by the interface area. Failure type was assessed under ×4 magnification.Statistical Analysis Data were statistically analyzed with a significance set at 5%. An analysis of variance test followed by the Games-Howell post-hoc test was used to compare the mean values between the groups and the interaction of the variables.Results The predominant failure type was cohesive, followed by mixed failure and adhesive in all groups. The apical third presented the highest bond strength (p < 0.05) regardless of the group, followed by the middle and coronal thirds. Overall, the SP PP group had the highest mean bond strength (p < 0.01), but the SP sealer was negatively affected by the IA drying protocol in the coronal and middle thirds. The BCS presented similar results within the third stage, regardless of the drying protocol.Conclusions Sealer Plus BC had a higher bond strength than Bio C Sealer, but it was negatively affected by the irrigation-aspiration protocol in the coronal and middle thirds. For the apical third, there was no difference between the groups; thus, a similar bond strength was observed regardless of the drying protocol or sealer.
Keywords: bioceramic sealers; endodontic sealer; bond strength; drying protocol; push-out test